Evaluasi Pelayanan Sistem Administrasi Manunggal Satu Atap Provinsi Riau di UPT Pengelolaan Pendapatan Simpang Tiga Kota Pekanbaru - Julianda, Nurafni; Syafhendry (UNIVERSITAS SERAMBI MEKKAH, 2025)
The purpose of this study was to determine and evaluate the Motor Vehicle Transfer Fee (BBNKB) service in the Riau Province One-Stop Integrated Administration System at the Simpang Tiga Revenue Management Unit in Pekanbaru City along with its inhibiting factors. This research method was qualitative, by conducting interviews with selected informants and the results were analyzed descriptively qualitatively. The results of the study showed that: 1) The Motor Vehicle Transfer Fee (BBNKB) service at the Simpang Tiga Revenue Management Unit in Pekanbaru City is still not fully optimal. This is due to several things, although the costs applied have referred to applicable regulations, the service process is still not optimal, especially in terms of completion time due to the limited number of officers who carry out physical vehicle checks. Lack of innovation in service, minimal socialization, and public perception that the BBNKB procedure is complicated and not urgent, especially for the management of BBNKB II for used vehicles, this further worsens the level of public compliance. Efforts made to improve services are still more oriented towards paying 1-year and 5-year taxes, while there has been no change in the BBNKB service. Many people still think that the requirements and procedures for managing motor vehicle transfer fees (BBNKB) are complicated and require large costs. 2) Inhibiting factors consist of low public awareness of paying BBNKB and the issue of eliminating BBNKB. Keywords: Evaluation; Services; BBNKB